2013
DOI: 10.1186/1479-5876-11-77
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implication of centrosome amplification and expression of centrosomal functional genes in multiple myeloma

Abstract: BackgroundMultiple myeloma (MM) is a low proliferative tumor of postgerminal center plasma cell (PC). Centrosome amplification (CA) is supposed to be one of the mechanisms leading to chromosomal instability. Also, CA is associated with deregulation of cell cycle, mitosis, DNA repair and proliferation. The aim of our study was to evaluate the prognostic significance and possible role of CA in pathogenesis and analysis of mitotic genes as mitotic disruption markers.Design and methodsA total of 173 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
(35 reference statements)
0
23
0
1
Order By: Relevance
“…Dementyeva et al (2010) found CA to be more frequent in B cells from MM patients when compared to those from healthy individuals. They also reported on the prognostic significance of the number of CA abnormalities and on the expression of centrosomal genes which were found to be downregulated in newly diagnosed (ND) patients, compared to relapsed patients (Dementyeva et al, 2013). In their study, ND MM patients with CA had a better prognosis compared to the CA negative group, indicating the clinical significance of centrosome clustering.…”
Section: Prognostic Role Of Dna Repair Defects and Genomic Instabilitymentioning
confidence: 96%
“…Dementyeva et al (2010) found CA to be more frequent in B cells from MM patients when compared to those from healthy individuals. They also reported on the prognostic significance of the number of CA abnormalities and on the expression of centrosomal genes which were found to be downregulated in newly diagnosed (ND) patients, compared to relapsed patients (Dementyeva et al, 2013). In their study, ND MM patients with CA had a better prognosis compared to the CA negative group, indicating the clinical significance of centrosome clustering.…”
Section: Prognostic Role Of Dna Repair Defects and Genomic Instabilitymentioning
confidence: 96%
“…Importantly, γ-tubulin is related to several human diseases. Levels of γ-tubulin are increased in various tumors, and inhibition of the GTPase activity of γ-tubulin in RB1-deficient tumor cells impedes tumor growth [ 24 , 25 , 56 , 77 , 78 , 79 , 80 , 81 , 82 ]. Mutations in the TUBG genes have also been found to cause brain malformations [ 54 , 83 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The previously used centrosome index (based on gene expression) demonstrates an association with poor prognosis in myeloma patients. In contrast, a more recent study (using immunofluorescent staining) indicates a better prognosis in newly diagnosed myeloma patients who are centrosome amplification positive [ 82 ]. The second mitotic kinase family are the polo-like kinases (1, 2, 3, 4 and 5).…”
Section: Deregulation Of the Cell Cycle In Multiple Myelomamentioning
confidence: 99%